Description of new cicada species associated with the coffee plant and an identification key for the species of Fidicinoides (Hemiptera: Cicadidae) from Brazil - Santos, Rodrigo Souza; Martinelli, Nilza Maria; Maccagnan, Douglas Henrique Bottura; Sanborn, Allen F.; Ribeiro, Renato (Zootaxa, 2010)
The genus Fidicinoides Boulard & Martinelli is characterized by its partially exposed timbal, not totally covered by the meta-scutellar plate as occurs in Fidicina Amyot & Serville, and has an extensive geographic distribution in Central and South America. In this work a new species for the genus is described. Fidicinoides sarutaiensis Santos, Martinelli & Maccagnan sp. n. is a medium-sized cicada, with the collected and studied specimens associated with coffee (Coffee arabica L.), in the municipality of Sarutaiá, in the southeast region of São Paulo state. The species F. glauca (Goding, 1925) and F. viridifemur (Walker, 1850) are transferred to Dorisiana. An identification key for the Fidicinoides species of Brazil is also proposed.